Peran Mediasi Perceived Value terhadap Repurchase Intention dalam Model S-O-R pada Produk Skincare - Dinda Agustina Fauziah; Surpiko Hapsoro Darpito (Journal of Business and Economics Research (JBE), 2026)
The facial care and beauty industry has experienced rapid growth driven by technological advancements and evolving consumer behavior. Azarine, as one of the popular skincare brands, has faced an overclaim issue that went viral on social media, triggering consumer skepticism and potentially reducing repurchase intention. Previous studies have reported inconsistent findings regarding the psychological mechanisms underlying the influence of brand image and online customer reviews on repurchase intention, particularly when incorporating perceived value as a mediating variable. This study aims to examine these relationships within the Stimulus-Organism-Response (SOR) framework using a quantitative approach with purposive sampling of 250 Azarine users in the Special Region of Yogyakarta, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that brand image (β = 0.473; p < 0.05) and online customer reviews (β = 0.472; p < 0.05) have a positive and significant effect on perceived value, while perceived value significantly influences repurchase intention (β = 0.673; p < 0.05). However, both variables do not have a direct significant effect on repurchase intention (brand image: y = 0.716; p = 0.474; online customer reviews: t = 1.147; p = 0.251). In contrast, the indirect effects through perceived value are significant (brand image: β = 0.319; t = 7.983; p < 0,05; online customer reviews: β = 0.317; t = 7.592; p < 0.05), indicating that perceived value acts as a full mediator in the model. These findings highlight the critical role of perceived value in driving repurchase intention and reinforce the Stimulus-Organism-Response (SOR) framework, where brand image and online customer reviews function as stimuli, perceived value as the organism, and repurchase intention as the response, implying that the effect of stimuli on responses occurs through consumers’ internal evaluation.